2010
DOI: 10.1007/s00018-010-0374-y
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of melatonin synthesis and MT1 receptor impairs the activation of Jurkat T cells

Abstract: Melatonin has been proposed as regulating the immune system by affecting cytokine production in immunocompetent cells, enhancing the production of several T helper (Th)1 cytokines. To further investigate the melatonin's role in IL-2/IL-2R system, we established an inducible T-REx expression system in Jurkat cells in which the protein levels of HIOMT enzyme or MT(1) receptor were significantly down-regulated upon tetracycline incubation. We found that T-REx Jurkat cells with lower levels of HIOMT activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…To further investigate the role of immune-derived melatonin in the IL-2/IL-2R system, HIOMT and MT 1 knock-down Jurkat cells were used. Both low levels of HIOMT activity and MT 1 expression diminished IL-2 production after phytohaemagglutinin (PHA) activation [52]. Colostrum immunocompetent cells produced a transient surge of melatonin after in vitro stimulation by enteropathogenic Escherichia coli or zymosan, suggesting the involvement of local melatonin in modulating the phagocytic capacity of the cells [26].…”
Section: Pineal-immune System Cross-talk: From the Pineal Gland Tomentioning
confidence: 99%
“…To further investigate the role of immune-derived melatonin in the IL-2/IL-2R system, HIOMT and MT 1 knock-down Jurkat cells were used. Both low levels of HIOMT activity and MT 1 expression diminished IL-2 production after phytohaemagglutinin (PHA) activation [52]. Colostrum immunocompetent cells produced a transient surge of melatonin after in vitro stimulation by enteropathogenic Escherichia coli or zymosan, suggesting the involvement of local melatonin in modulating the phagocytic capacity of the cells [26].…”
Section: Pineal-immune System Cross-talk: From the Pineal Gland Tomentioning
confidence: 99%
“…With MT1 and MT2 receptors, melatonin was found to inhibit the production of forskolin-stimulated cyclic AMP (cAMP), cyclic GMP (cGMP) and diacylglycerol (DAG), leading to the improved immunity [183,184]. Besides, the specific nuclear melatonin receptors have been identified in Jurkat cells [185], lymphocytes [186], thymus [175] and spleen [187], which belong to the RZR/ROR subfamily of nuclear receptors.…”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%
“…In vivo evidence from a study using broiler chickens showed that proliferation of T cells in their thymus is positively correlated with concentrations of melatonin in the plasma, while pinealectomy, which reduces melatonin levels in the blood, or the use of antagonists to MT1 decreases the proliferation of T cells . Direct evidence that melatonin activates T cells was provided by a study which demonstrated that inhibiting HIOMT in PHA‐activated Jurkat cells reduces production of melatonin and IL‐2 . Similarly, exogenous melatonin promotes the proliferative activity of T cells, while antagonists of MT1 limit their proliferation .…”
Section: Melatonin and Activation Of T Cellsmentioning
confidence: 99%
“…The administration of luzindole (a high‐affinity antagonist for MT1/MT2) to mice inhibited the ability of melatonin to stimulate proliferation of splenic lymphocyte in response to the T‐cell mitogen concanavalin A . Furthermore, inhibition of MT1 decreased the production of IL‐2 by PHA‐activated Jurkat cells and their expression of the early activation marker CD25 . Both luzindole and CGP 55644 significantly inhibit IL‐2 production by Jurkat cells .…”
Section: Mechanisms Whereby Melatonin Affects T‐cell Biologymentioning
confidence: 99%